Individual characteristics and career exploration in adolescence - Taveira, Maria do Céu (1998)
The effects of gender, age and school grade on several career exploration dimensions measured by the Career Exploration Survey were investigated. Subjects were high school students facing an imminent career decision. Regression analyses indicated that sex and grade-level were the most significant and prevailing individual characteristics related to the adolescents’ career exploration behaviours, reactions and beliefs. Implications for career exploration interventions are discussed.